Comparison capacity of collagen hydrogel, mix‐powder and in situ hydroxyapatite/collagen hydrogelscaffolds with and without mesenchymal stem cells and platelet‐rich plasma in regeneration of critical sized bone defect in a rabbit animal model. Issue 12 (18th May 2021) - Bakhtiarimoghadam, Behnam; Shirian, Sadegh; Mirzaei, Esmaeil; Sharifi, Siavash; Karimi, Iraj; Gharati, Gelavizh; Takallu, Sara; Nazari, Hassan
Abstract: The aim of this study was to investigate the effect of developed collagen (Co) hydrogel (CH), powder‐mixed hydroxyapatite/collagen (HA/Co) hydrogel and in situ synthesized HA/Co (In/HA/Co) hydrogel with or without mesenchymal stem cell (MSC) and platelet‐rich plasma (PRP) on the regeneration of full‐thickness critical size bone defect in the rabbit animal model. In the first step of this study, the scaffolds were synthesized and characterized using FTIR spectroscopy, X‐ray diffraction, and scanning electron microcopy. In the second step or animal study, the radial bone defects were filled with the synthesized scaffolds with and without MSC and PRP. One hundred sixty one year‐old New Zealand white male rabbits were randomly divided in 16 groups of 10 rabbits including control with bone defect without treatment, In/HA/Co, HA/Co, CH, PRP, MSC, CH + PRP, HA/Co, In/HA/Co + PRP, HA/Co + PRP, CH + MSC, In/HA/Co + MSC, HA/Co + MSC, CH + PRP + MSC, In/HA/Co + PRP + MSC, and HA/Co + PRP + MSC. The created defects were filled using the constructed scaffolds alone or seeded with MSCs, with and without PRP injection. The treatments were assessed using histopathological, immunohistochemical and rediographical analysis on days 14, 28, 42, 56 post‐treatment. The plate‐like HA particles were distributed homogeneously in the in situ HA/Co scaffold compared to the HA/Co scaffold and had a similar structure to bone with carbonated plate‐like HA particles and nanofibrilated Co matrix. In situ HA/Co nanocomposite seeded with MSC and enriched by PRP can accelerate bone regeneration resulted from osteoblastic production of osteocalcin protein. Therefore, in situ HA/Co hydrogel seeded with MSC and PRP can be a new approach for bone tissue engineering.